The AIMSS Project - I. Bridging the star cluster-galaxy divide - Norris, Mark A.; Kannappan, Sheila J.; Forbes, Duncan A.; Romanowsky, Aaron J.; Brodie, Jean P.; Faifer, Favio Raúl; Huxor, Avon P.; Maraston, Claudia; Moffett, Amanda J.; Penny, Samantha J.; Pota, Vincenzo; Smith-Castelli, Analía; et al. (Monthly notices of the Royal Astronomical Society, 2014)
Abstract. We describe the structural and kinematic properties of the first compact stellar systems discovered by the Archive of Intermediate Mass Stellar Syste
Published: 21 July 2014
Gesehen am 03.09.2020